2020
DOI: 10.1101/2020.10.19.20213975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact on microbiology laboratory turnaround times following process improvements and total laboratory automation

Abstract: Introduction: The impact of workflow changes and total laboratory automation (TLA) on microbiology culture processing time was evaluated in an academic-affiliated regional hospital. Materials and Methods: A retrospective analysis of microbiological data in a research database was performed to compare turnaround time (TAT) for organism identification (ID) before and after implementation of TLA (2013 versus 2016, respectively). TAT was compared using chi-squared test for categorical variables and log-transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, successful implementation of laboratory automation requires thorough assessment and appropriate refinement of laboratory workflow practices that might impact system efficiency. 10, 12, 13, 29, 30 This study provides a comprehensive evaluation of the time and steps required with a modular Kiestra-enabled automation workflow in comparison with manual processes. Utilization of the Kiestra automation system (InoqulA and ReadA) led to 88% fewer media plate touches, 85% less HOT, and 69% less TTT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, successful implementation of laboratory automation requires thorough assessment and appropriate refinement of laboratory workflow practices that might impact system efficiency. 10, 12, 13, 29, 30 This study provides a comprehensive evaluation of the time and steps required with a modular Kiestra-enabled automation workflow in comparison with manual processes. Utilization of the Kiestra automation system (InoqulA and ReadA) led to 88% fewer media plate touches, 85% less HOT, and 69% less TTT.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 To address these and other common problems encountered in the clinical laboratory, automation can be employed to streamline and standardize laboratory workflows. Several studies have shown improved laboratory workflow efficiency, 3-5, 10, 12-16 result reproducibility, 4,5,13,[15][16][17][18][19] and decreased incidence of errors 10,13,[18][19][20][21] following the implementation of automation-related processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations